2005
DOI: 10.1080/00220380500092754
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Development Contribute to Poverty Reduction?

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(146 citation statements)
references
References 26 publications
7
127
2
3
Order By: Relevance
“…Financial globalization and the widespread consensus on the positive interplay between growth and development of the financial sector incited scholars to research the influence that improvements within the financial sector have on inequality and poverty. Positions in academic literature have generally suggested that improvements in the financial sector contribute to poverty alleviation (Beck et al, 2004;Jalilian and Kirkpatrick, 2005;Perez-Moreno, 2011;Sehrawat and Giri, 2016). However, the findings on finance-inequality have remained inconclusive.…”
Section: Review Of Empirical Literaturementioning
confidence: 96%
“…Financial globalization and the widespread consensus on the positive interplay between growth and development of the financial sector incited scholars to research the influence that improvements within the financial sector have on inequality and poverty. Positions in academic literature have generally suggested that improvements in the financial sector contribute to poverty alleviation (Beck et al, 2004;Jalilian and Kirkpatrick, 2005;Perez-Moreno, 2011;Sehrawat and Giri, 2016). However, the findings on finance-inequality have remained inconclusive.…”
Section: Review Of Empirical Literaturementioning
confidence: 96%
“…This argues for the need to expand service provision towards the unbanked and those on low incomes and away from the focus of microfinance on providing financial services to poor people. This shift is supported by research that suggests that the poverty reducing effects of financial sector development on poverty reduction lie mainly through the indirect effects on growth rather than the effects of direct access for poor people to financial services (Beck, et al 2007;Honohan 2007;Jalilian and Kirkpatrick 2005). This argument is further supported by the view that the distinction between microfinance and banking provision has been overdrawn (Honohan 2004), and also by recent shifts of microfinance provision towards individually rather than group-based products, and their transformation into regulated institutions.…”
Section: Inclusive Financial Markets: the Policy Contextmentioning
confidence: 97%
“…One reason for this ambiguity in research is the lack of data and the shortcomings of statistical methods regarding their interpretation and analysis (see Arestis and Demetriades, 1997). Another reason can be seen in the complexity of the relationship itself, as financial development may not only influence inequality and poverty directly, but also indirectly, for instance, via its effect on economic growth (Jalilian and Kirkpatrick, 2005). Figure 1 shows the direct and indirect mechanisms of financial development on poverty and inequality.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Starting with the indirect impact of financial development on inequality through the economic growth channel, a positive link between financial development and economic growth is widely agreed upon (Goldsmith, 1969;McKinnon, 1973;Shaw, 1973;Bencivenga and Smith, 1991;King and Levine, 1993;Beck et al 2004;Jalilian and Kirkpatrick, 2005). Possible causes for the positive impact of financial development on economic growth are allocation of savings and total factor productivity growth (Schumpeter, 1959) as well as capital allocation (King and Levine, 1993).…”
Section: Figure 1 Financial Development Economic Growth Inequalitymentioning
confidence: 99%
See 1 more Smart Citation